2010
DOI: 10.1007/s12072-010-9190-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of small liver nodules detected by computed tomographic angiography in patients with hepatocellular carcinoma

Abstract: Purpose Hepatic lesions identified by computed tomography (CT) during arterial portography (CTAP) or CT hepatic arteriography (CTHA) in hepatocellular carcinoma (HCC) patients are sometimes too small to be diagnosed as HCC. We undertook this cohort study to assess whether these small lesions are actually HCC, and to clarify the effectiveness of these imaging examinations in a clinical setting. Methods We assessed the characteristics of 74 tiny lesions detected by CTAP and/or CTHA, but not by CT in 67 patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Additionally, small HCC is associated with relatively benign behavior: Smaller lesions are less likely to show microvascular invasion , and nodules <3 cm were found not to be significantly associated with hepatic seeding of HCC . Single‐center longitudinal studies from Japan and San Francisco as well as a study modeling growth rates reported that most patients with early‐stage HCC do not progress rapidly for approximately six months after being placed on the transplant wait‐list.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, small HCC is associated with relatively benign behavior: Smaller lesions are less likely to show microvascular invasion , and nodules <3 cm were found not to be significantly associated with hepatic seeding of HCC . Single‐center longitudinal studies from Japan and San Francisco as well as a study modeling growth rates reported that most patients with early‐stage HCC do not progress rapidly for approximately six months after being placed on the transplant wait‐list.…”
Section: Discussionmentioning
confidence: 99%
“…64 lesions were followed up and 18 of these increased in size and showed typical features of HCC. 28 HCC is the sixth most common cancer in the world. 29 Though histopathological diagnosis is the gold standard; the liberty of biopsy is not always available.…”
Section: Resultsmentioning
confidence: 99%
“…CT arteriography (CTA) can be used to detect hepatocellular carcinomas (HCC) and their feeding arteries (1). For effective transarterial chemoembolization (TACE), the position and shape of the tumor and its feeding arteries must be known.…”
Section: Introductionmentioning
confidence: 99%